An Electrochemical DNA Sensing Platform Using Carboxyl Functionalized Graphene as the Electrode Modified Material. Issue 6 (1st April 2017) - Cheng, Dan; Yang, Linlin; Li, Xi; Zhou, Jian; Chen, Qi; Yan, Songling; Li, Na; Chu, Mei; Dong, Yulin; Xie, Zhizhong; Zhang, Chaocan
Abstract : With the expected characteristics of both promoting electric transfer rate and immobilizing -NH2 labeled probe for the construction of electrochemical sensing platform for DNA determination, the carboxyl functionalized graphene (CFGR-COOH) was carried out from the carboxylation of graphene oxide (GO), partly reduction, addition of cyan groups (–CN). The X-ray photoelectron spectroscopy (XPS) results indicated the successfully prepared expected materials. Three kinds of novel electrochemical DNA biosensors were developed at CFGR-COOH modified glassy carbon electrode (CFGR-COOH/GCE), targeting at identifying specific DNA, the CFGR-COOH and PANI modified platinum electrode (CFGR-COOH/PANI/Pt), aiming at the further increase for the electrochemical performance of the prior biosensor with the synergistic effect between those two materials, and the hairpin probe/ horseradish peroxidase (HRP) labeled CFGR-COOH/GCE, which was constructed to prove the promise utilization of CFGR-COOH in various sensing platforms. Through the differential pulse voltammetry (DPV) detection, the linear ranges of 1.0 × 10 −6 to 1.0 × 10 −13 mol·L −1, 1.0 × 10 −6 to 1.0 × 10 −14 mol·L −1 and 1.0 × 10 −6 to 1.0 × 10 −10 mol·L −1 were obtained for the above biosensors, coupling with the detection limits of 4.0 × 10 −14 mol·L −1, 5.8 × 10 −15 mol·L −1 and 7.0 × 10 −11 mol·L −1, respectively. The as-prepared CFGR-COOH showed potential application prospect as a valuable modification material in DNA sensing platforms.